STUDIES ON HETEROSIS FOR YIELD IN BRINJAL (Solanum melongena. L) - K. R. SARAVANAN, G. KALAIYARASI, S. RANJITH RAJA RAM, (Horticultural Biotechnology Research)
Heterosis breeding is one of the most efficient tools to exploit the heterotic response for various useful traits. The Line × Tester mating design was undertaken with seven lines and three testers were evaluated along with twenty one hybrids in randomized block design to estimate the magnitude of heterosis for yield and its yield contributing characters. The best way to utilize heterosis in crop is to generate F1 hybrids having maximum heterozygocity, thereby facilitating the identification and selection of hybrid vigor. The positive significant standard heterosis for fruit yield per plant was maximum with L3 × T1 (28.94%) followed by L7 × T3 (15.73%) and L7 × T1 (15.10%) respectively. Some of the promising hybrids have showed desirable heterosis for plant height, number of fruits per plant,1000 seed weight, seedling shoot length, seedling root length and seedling dry weight.